Entrainer for batch distillation of acetic acid -water system - Gadekar, S. V.; Naik, R. V.; Kaul, S. N. (Journal of Scientific & Industrial Research, 2009)
Acetic acid-water system (AW) poses a challenge in reactive distillation, acetic acid purity and loss of acetic acid in aqueous solutions. Feasible separation of AW has been studied using entrainers but acetic acid loss in lean phase cannot be avoided. This study presents feasible region to operate column with toluene and benzene as entrainer for AW. Liquid-liquid equilibrium data and nature of tie line for ethyl acetate are given priority.
Keywords: Acetic acid; Batch distillation; Benzene; Entrainer; Toluene